Diels–Alder reactions of 3-(1H-tetrazol-5-yl)-nitrosoalkenes: synthesis of functionalized 5-(substituted)-1H-tetrazoles - Lopes, Susana M. M. (2012)
A general route to 1,2-oxazines and open chain oximes bearing a 1H-tetrazolyl substituent via DielseAlder reaction of 3-(tetrazol-5-yl)-nitrosoalkenes is reported. It was also demonstrated that reduction of these adducts followed by deprotection of the tetrazolyl group give 5-(1-aminoalkyl)-1H-tetrazoles, a-amino acid analogues.